Reflections on the theoretical advance in ethnobiology: are we pointing to the wrong direction? - Ferreira Júnior, Washington Soares (Ethnobiology and Conservation, 2020)
Over the past 30 years, a series of ethnobiological studies has presented and discussed theoretical scenarios, new hypotheses to be tested, as well as relevant research questions based on dialogue with different disciplines. However, the production of these articles of important theoretical relevance has not accompanied an increase in the number of studies that contribute to the advancement of scientific knowledge in ethnobiology. In this manuscript, I discuss some of the main reasons that can lead to the large number of works that reflect little on their theoretical contributions, with the aim to minimize these problems, so we can favor the progress in the area for the coming years.